2018
DOI: 10.1007/s40257-018-0354-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Therapeutic Aspects of Linear Psoriasis: A Study of 30 Cases

Abstract: We identified a wide range of LP, with two profiles: isolated LP and superimposed LP. Topical treatment usually evoked clinical response, with relative resistance to systemic therapy. Methotrexate and anti-tumor necrosis factor (TNF)-α therapies can possibly unmask LP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our research further updated the clinical characteristics of BLP. Compared with a study involving 30 patients with BLP conducted in France 6 years ago [ 3 ], we have agreements as well as new findings. The consistent aspects include earlier onset, unilateral distribution (no preference for left or right side), and triggering/aggravation factors (in about one-third of patients with BLP).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our research further updated the clinical characteristics of BLP. Compared with a study involving 30 patients with BLP conducted in France 6 years ago [ 3 ], we have agreements as well as new findings. The consistent aspects include earlier onset, unilateral distribution (no preference for left or right side), and triggering/aggravation factors (in about one-third of patients with BLP).…”
Section: Discussionsupporting
confidence: 76%
“…BLP can be the only manifestation of psoriasis (type I, or isolated type), or it can be superimposed in less severe disseminated classical lesions of psoriasis vulgaris, and unmasked when classical lesions fade away with antipsoriatic treatment (type II, or superimposed type) (Fig. 1 c) [ 2 , 3 ]. The term “superimposed type” was introduced in 2007 to highlight the distinction between polygenic and monogenic susceptibility backgrounds [ 4 ], which can help to elucidate the molecular basis of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a case of superimposed LP was reported when using methotrexate in two patients, infliximab in one patient and ethanol in one patient. 5 LP development has also been reported in a patient who has been using lithium 900 mg for 3 months due to bipolar disorder. 6 According to our research, there are no reported cases of LP related to sekukinumab in the literature.…”
mentioning
confidence: 75%
“…Previous studies have reported that psoriasis often lead to increased risks of comorbidities, such as inflammatory arthritis, obesity, hypertension, and inflammatory bowel disease [2]. Unfortunately, the incidence of psoriasis is increasing year by year, with approximately 2-4% of population suffering from this disease in the world [3]. Current treatments of psoriasis mainly include topical therapy [4], phototherapy [5], immunotherapy [6], and systemic therapy [7].…”
Section: Introductionmentioning
confidence: 99%